A cross sectional study to understand socio demographic profile of patients of sickle cell anemia in a Taluka of South Gujarat - Gamit, Chintan; Patni, MohamedAnas M.; Gamit, Sukesha (International Journal Of Community Medicine And Public Health, 2017)
Background: India has the largest concentration of tribal populations globally. A high prevalence of sickle cell anemia is seen in tribal communities of South Gujarat. The aims and objectives were to study socio- demographic profile of the patients having positive sickle cell status. Methods: It was a cross-sectional study, where Bardoli taluka was selected purposively. All patients of sickle cell anemia registered at all PHCs of Bardoli Taluka during period between June 2010 and May 2011 & aged between 18 to 30 years were taken in study. Results: This study included total 276 cases of which 264 (96%) had sickle cell trait, while 12 (4%) had sickle cell disease. Majority of patients were from Umrakh and Vanskui PHC. More than 90% of patients belonged to ST caste and more than 40% among them were from Rathod sub caste. Conclusions: More than 90% of patients were laborers and majority of them belonged to low socio economic class. Mean age at diagnosis of sickle cell anemia ranged from 21 to 25 years.